Histopathology of seed stalk necrosis of onion caused by Erwinia herbicola, with special reference to colonization - Mansvelt, E. Lucienne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1982.